Todd McFarlane's Spider-Man - McFarlane, Todd 1961- (IDW Pubishing, 2022)
This Artist's edition features selected pages from Todd McFarlane's run on Amazing Spider-Man (299-328), Spider-man (1-14) as well as cover art from Spider-Man and other Marvel titles. Pages reproduce the original comic art with visible edits and blue line notes and comments
Keywords: Spider-Man -- Fiktive Gestalt; Spider-Man / (Fictitious character) / Comic books, strips, etc; Comic books, strips, etc / Illustrations; Superheroes / Comic books, strips, etc; Spider-Man / (Fictitious character); Science fiction comic books, strips, etc; Superheroes; Comics (Graphic works); Superhero comics; Illustrated works; Comic